Photostability Studies and Development of Fast Release Nifedipine Tablets - M.A. SHENDE,; T. MARKANDEEYWAR, (International Journal of Pharma and Bio Sciences, 2010)
In the present study, an attempt has been made to improve the physiochemical stability of nifedipine by complexation using weak cation-exchange resins, indion 204 and indion 264 to eliminate light decomposition tendency of drug. Tablets were prepared by Indion 204: drug complex using optimized ratio with different diluents. Irradiation test for drug degradation was carried out by comparing pure nifedipine drug, methanolic drug solution, resinates and prepared tablets formulation to determine differences in the effectiveness of artificial light and natural indirect sunlight sources. The tested resinate of nifedipine and optimized formulation was likely to be photostable up to at least 10 weeks of continuous artificial and natural day light exposure. In-vitro drug release studies showed more than 90% drug release within 30 min and exhibited similar dissolution profile with commercial tablets. Indion 204 was found to be better complexing agent for reducing the photosensitivity and to design stable nifedipine tablets.